Experience of suffering in patients with hypertension: a qualitative analysis of in-depth interview of patients in a university hospital in Seoul, Republic of Korea - Jidong Sung; Young-gyung Paik (BMJ Open)
Objective To describe the suffering experienced by patients with hypertension, not only regarding symptoms, but also suffering in a social context.Design A qualitative analysis of semi-structured interview data. Interviews were audio-recorded and transcribed verbatim. A descriptive approach was taken by exploring patient accounts and presenting their experiences and perspectives.Setting Cardiology clinic in a university hospital (Samsung Medical Center, Seoul, Republic of Korea).Participants Patients with hypertension and without serious comorbidities who had been followed-up at a cardiology clinic of a training university hospital.Results Nineteen men and women (male:female=12:7) were interviewed. The mean age was 44 years, and the average hypertension duration was 4 years. All 19 patients reported symptoms allegedly to be associated with hypertension. Anxiety about blood pressure fluctuation and hypertension complications, dislike of antihypertensive medication and associated labelling effect, family stress and refusal to be enrolled in life insurance were commonly found among patients’ interviews. Relatively younger (≤50 years of age), actively working patients experienced stigmatisation and discrimination in the workplace.Conclusion The illness experience of patients with hypertension consists of suffering associated with threatened or damaged self-identity at the individual and social level. Medical professionals should have more awareness of the suffering of these patients to improve the quality of care. An education programme with proper focus on the elements of patients’ suffering may help to alleviate it.